Strategic development of flipped framework on educators and learning constructs for ESL context: the experts’ agreement - Mohammad Musab, Azmat Ali; Melor, Md Yunus; Harwati, Hashim; Azwin Arif, Abdul Rahim; Nor Yazi, Khamis (Human Resource Management Academic Research Society (HRMARS), 2019)
The flip learning approach has been accepted by numerous studies as a strategic approach in implementing technological-based classroom environments. Concurrently, Ministry of Education Malaysia is introducing the national educational blueprint for higher education with the focus on heavy investment in developing Blended learning environments at tertiary institutions. This poses a conundrum of how best to implement such environments effectively. Hence, much researches needed to be empirically done to prove the effectiveness of a specific Blended learning approach for an ESL context. This paper aims to ascertain the required constructs in developing a framework for flipped learning in an ESL environment. The study utilized Fuzzy Delphi method to gather and analyze viewpoints of 18 experts from the relevant fields. An online questionnaire was developed to gather the experts’ agreement towards four educators and learning related constructs namely ‘Flexible Environments’; ‘Shift in Learning Culture’; ‘Intentional Content’; ‘Professional Educators’; and 42 items gathered from the literature. The FDM analysis rejected six of the items; finalizing the framework with 36 items. The framework is beneficial to ESL educators, learners and developers of technology-based learning methods